Elucidation of quorum quenching and mutualistic interaction of green microalga Chlorella sp. and Bacillus sp. BpChlAY for biocontrol of vibriosis in aquaculture - Yahya, Nur Ain (2020)
Vibriosis are among the bacterial diseases that lead to massive mortality in cultured marine fish and shellfish limiting the sustainable development of aquaculture production. It is widely reported that Vibrio regulates its virulence factors through quorum sensing (QS), a cell-to-cell communication system mediated by small signal molecules produced by the pathogen in response to population density. Therefore, inhibiting QS, also known as quorum quenching (QQ) could prevent the regulation of virulence factors and is suggested as an alternative solution for biocontrol of vibriosis in aquaculture. The objectives of this study were to screen and identify QQ candidates from marine microalgae and their associated bacteria; to evaluate the effects of bacterial quenchers on microalgal growth and QQ activity in small flask (100 mL) and photobioreactor (100 L) scales; and to tentatively identify compounds with QQ properties. In the first part of this study, out of the 17 marine microalgae screened for QQ activity, only Chlorella sp. showed QQ activity by inhibiting the acyl-homoserine lactone (AHL) regulated phenotypes of purple violacein production in QS reporter Chromobacterium violaceum CV026 and autoinducer-2 (AI-2) regulated phenotypes of bioluminescence in Vibrio campbellii BB120 and its double mutant strain V. campbellii JMH597 without inhibiting the reporters’ growth. Meanwhile, seven bacterial strains were successfully isolated from Chlorella sp., Pavlova sp., Spirulina sp. and Nannochloropsis sp. using N-hexanoyl-L-homoserine lactones (HHLs) enrichment method. Three of the bacteria, identified as Bacillus sp. BpChlAY, Bacillus sp. BpNofAY and Bacillus sp. BpSpiAY isolated from Chlorella sp., N. oculata and Spirulina sp., respectively, inhibited purple production of C. violaceum CV026, without affecting the reporter’s growth. The cells of Bacillus sp. BpChlAY, Bacillus sp. BpNofAY and Bacillus sp. BpSpiAY were able to fully degrade 10 ppm of HHLs within 6 to 9 hours. However, none of their supernatants showed degradation activity. In vivo challenge test using Artemia franciscana as a model organism was carried out to evaluate the effects of Chlorella sp., Bacillus sp. BpChlAY, Bacillus sp. BpNofAY and Bacillus sp. BpSpiAY towards Artemia survival when challenged with QS-dependent pathogen V. campbellii BB120. The results showed that the live cells of Chlorella sp., live cells of Bacillus sp. BpChlAY and the combination of Chlorella sp. and Bacillus sp. BpChlAY significantly (P<0.05) improved Artemia survival towards V. campbellii. It is interesting to note that the Bacillus sp. BpChlAY was capable to reduce AHL and AI-2 regulated luminescence of the double mutant QS reporter V. campbellii JMH612 and V. campbellii JMH597, respectively. In the second part of this study, a co-culture experiment between Chlorella and each of the Bacillus sp. BpChlAY, Bacillus sp. BpNofAY and Bacillus sp. BpSpiAY was conducted in 100 mL culture volume for 14 days to determine the effects of bacterial quenchers towards Chlorella growth and its QQ activity. Out of the three bacterial strains, Bacillus sp. BpChlAY enhanced the Chlorella growth compared to Bacillus sp. BpNofAY and Bacillus sp. BpSpiAY. However, no QS degradation was observed in C. violaceum CV026 using the extracts from all treatments of the small-scale co-culture. Due to the positive effects towards Artemia survival and Chlorella growth, Bacillus sp. BpChlAY was co-cultured further with Chlorella in photobioreactor scale (100 L culture volume) for 45 days. The results showed that the addition of Bacillus sp. BpChlAY led to an increase in Chlorella growth up to 1.8-fold in terms of dry weight and 3.9-fold in both Chlorella cell density and in vivo chlorophyll fluorescence. The QQ activity of Chlorella was also improved in the presence of Bacillus sp. BpChlAY compared to Chlorella without Bacillus sp. BpChlAY after 45 days cultivation at the late stationary growth phase. No difference in QQ activity with or without the co-cultivation of the microalga and the bacteria at stationary stage of 25 days culture. In the last part of this study, the extracts of Chlorella from thin layer chromatography fraction (Chapter 3); and from photobioreactor (Chapter 4) with and without Bacillus sp. BpChlAY that were harvested at four different algal growth phases of lag, log, stationary and late stationary were tentatively identified using Ultra- High Performance Liquid Chromatography Electrospray Ionization Mass Spectrometry (UHPLC-ESI-MS). It was observed that there are no differences between the metabolite identities from the two Chlorella treatments. However, analysis of UHPLC-ESI-MS showed apparent molecular and fragment ions, which were consistent with 25 tentative metabolites identified and belonged to classes of tripeptides, lipid and lipid-like molecules, benzenoids, flavonoids, carbohydrates, lactones, quinolines and benzimidazoles. It is therefore concluded that both Chlorella and Bacillus sp. BpChlAY exhibited probiotic characteristics through AHL and AI-2 degradation activities, and are able to protect A. franciscana from V. campbellii. The bacteria also promote the Chlorella growth and enhanced QQ activity particularly at a later stage. The identification of Chlorella extracts with and without Bacillus sp. BpChlAY showed that it consisted of a wide range of biologically active compounds’ classes. The combination of both partners, thus, constitute natural QQ probiotics that could be used to control vibriosis in aquaculture.